Seasonal Expression of the Picocyanobacterial Phosphonate Transporter Gene phnD in the Sargasso Sea - Ilikchyan, Irina N.; Mckay, Robert M.; Kutovaya, Olga A.; Condon, Rob; Bullerjahn, George S. (Frontiers in Microbiology, 2010)
In phosphorus-limited marine environments, picocyanobacteria (Synechococcus and Prochlorococcus spp.) can hydrolyze naturally occurring phosphonates as a P source. Utilization of 2-aminoethylphosphonate (2-AEP) is dependent on expression of the phn genes, encoding functions required for uptake and C-P bond cleavage. Prior work has indicated that expression of picocyanobacterial phnD, encoding the phosphonate binding protein of the phosphonate ABC transporter, is a proxy for the assimilation of phosphonates in natural assemblages of Synechococcus spp. and Prochlorococcus spp (Ilikchyan et al. 2009). In this study, we expand this work to assess seasonal phnD expression in the Sargasso Sea. By RT-PCR, our data confirm that phnD expression is constitutive for the Prochlorococcus spp. detected, but in Synechococcus spp., phnD transcription follows patterns of phosphorus availability in the mixed layer. Specifically, our data suggest that phnD is repressed in the spring when P is bioavailable following deep winter mixing. In the fall, phnD expression follows a depth dependent pattern reflecting depleted P at the surface following summertime drawdown, and elevated P at depth.